India's film society movement: the journey and its impact - Cherian, V. K. (SAGE, 2017)
First comprehensive account of the seven-decade long journey of the Film Society Movement in India, and how it helped Indian cinema come into its own
https://katalog.adlr.link/Record/0-872511669